Design of Chicken Egg Farm based on the IoT in Padamulya Ciamis Village, West Java, Indonesia - Sambas, Aceng; Firdaus, Aef Ridwan; Mujiarto, Mujiarto; Gundara, Gugun; Mulyati, Neneng Sri (Research Collaboration Community (Rescollacom), 2025)
The development of smart farming using the Internet of Things (IoT) has significantly improved efficiency in various agricultural sectors, including poultry farming. This community service project aims to design and implement an IoT-based chicken egg farm in Padamulya Ciamis Village, West Java, Indonesia. The system integrates smart sensors and automated controls to monitor environmental parameters such as temperature, humidity, and feed levels, ensuring optimal conditions for egg production. Data collected in real-time will be accessible through a cloud-based platform, allowing farmers to make informed decisions to enhance productivity. This initiative is expected to improve farm efficiency, reduce manual labor, and serve as a model for sustainable poultry farming in rural areas.